Specificity traits consistent with legume-rhizobia coevolution displayed by Ensifer meliloti rhizosphere colonization - Salas, María Eugenia (2017)
Rhizobia are α‐ and ß‐proteobacteria that associate with legumes in symbiosis to fix atmospheric nitrogen. The chemical communication between roots and rhizobia begins in the rhizosphere. Using signature‐tagged‐Tn5 mutagenesis (STM) we performed a genome‐wide screening for Ensifer meliloti genes that participate in colonizing the rhizospheres of alfalfa and other legumes. The analysis of ca. 6,000 mutants indicated that genes relevant for rhizosphere colonization account for nearly 2% of the rhizobial genome and that most (ca. 80%) are chromosomally located, pointing to the relevance and ancestral origin of the bacterial ability to colonize plant roots. The identified genes were related to metabolic functions, transcription, signal transduction, and motility/chemotaxis among other categories; with several ORFs of yet‐unknown function. Most remarkably, we identified a subset of genes that impacted more severely the colonization of the roots of alfalfa than of pea. Further analyses using other plant species revealed that such early differential phenotype could be extended to other members of the Trifoliae tribe (Trigonella, Trifolium), but not the Fabeae and Phaseoleae tribes. The results suggest that consolidation of E. meliloti into its current symbiotic state should have occurred in a rhizobacterium that had already been adapted to rhizospheres of the Trifoliae tribe.